Jewish Germany an enduring presence from the fourth to the twenty-first century - Levinson, David 1947- (Vallentine Mitchell, 2018)
Cultural anthropologist David Levinson draws out and explores for us the expanse of the Jewish experience in Germany from the fourth century CE to the present. With the extensive use of primary sources, among others, the carefully researched narrative takes us smoothly and chronologically through the complete history of Jews in Germany. Details about all aspects of Jewish life are placed within their political and economic contexts to enhance our understanding of the variety and complexity of the Jewish experience in Germany and the adaptive requirements of Jewish communities in changing circumstances. Moving back and forth between the general and the particular, Jewish Germany gives us a layered appreciation of the Jewish experience, enriched with details about Jewish life in the eighteenth century, a period when German communities re-formed after the end of the Thirty Years War, and nineteenth, when Jews in Germany moved toward emancipation. Levinson also calls upon his own family history as the entry point for exploration of Jewish life in several Jewish communities, most important among them the town of Uehlfeld in Middle Franconia and the city of Frankfurt am Main. Jewish Germany is essential for anyone interested in possessing a greater understanding of and more information about this history from the budding genealogist tracing her family history, to the general reader looking for a broad overview, to scholars who might wish for further knowledge and explanatory material on the history and diverse experiences of Jewish communities in Germany before the Holocaust
Keywords: Geschichte; Juden; Deutschland